Review: In the Shadow of the Holocaust: Nazi Persecution of Jewish-Christian Germans - Griech-Polelle, Beth A. (Holocaust and genocide studies, 2005)
In the Shadow of the Holocaust: Nazi Persecution of Jewish-Christian Germans James F. Tent Lawrence University Press of Kansas 2003 288 $ 29.95